2020
DOI: 10.1002/acn3.51061
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study on nerve ultrasound and corneal confocal microscopy in NF155 paranodopathy

Abstract: We report the case of a 27‐year‐old patient with subacute anti‐neurofascin‐155 neuropathy with bifacial palsy, who showed excellent response to rituximab. We provide longitudinal data of established clinical scores, nerve conduction studies, antibody titers, and novel imaging methods (nerve ultrasonography and corneal confocal microscopy). Clinical and electrophysiological improvement followed the reduction of serum antibody titer and correlated with a reduction of corneal inflammatory cellular infiltrates whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…This good response to RTX is in accordance with the literature. 6 , 8 , 35 40 Therefore, RTX should be considered for patients with autoantibody related disease.…”
Section: Discussionmentioning
confidence: 99%
“…This good response to RTX is in accordance with the literature. 6 , 8 , 35 40 Therefore, RTX should be considered for patients with autoantibody related disease.…”
Section: Discussionmentioning
confidence: 99%
“…Only few data are available concerning imaging of paranodopathies, but the pattern seems to be similar to that seen in typical CIDP, probably more often affecting cranial nerves [ 78 , 79 ].…”
Section: Immune-mediated Neuropathiesmentioning
confidence: 98%
“…CCM was also useful to detect CIDP in those individuals with and without coexisting diabetes, indicating that the increase in dendritic cells is driven by peripheral nerve inflammation. Indeed, recent longitudinal studies have shown that increased dendritic cell infiltration may predict worsening outcomes in CIDP [ 24 ] and infiltrates may be reduced in response to immune therapy [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective study of 17 individuals with CIDP who were followed over 18 months, the presence of > 30 cells/mm 2 at baseline identified clinical progression with a sensitivity and specificity of 100% [ 24 ]. Moreover, in one person with anti-neurofascin-155 neuropathy, treatment with rituximab was associated with a reduction in the serum antibody titer with a clinical and electrophysiological improvement and reduction of corneal inflammatory cell infiltrates [ 25 ].…”
Section: Introductionmentioning
confidence: 99%